Managers’ propensity to take risk in project selection decisions: the effect of payoff magnitude - Kevin Baird; Sujatha Perera; Ting T. Meng (Australasian Accounting, Business and Finance Journal, 2008)
This paper examines the factors that influence managers’ propensity to take risk in project selection decision contexts with a special focus on payoff magnitude as an influencing factor. This study utilises an experimental research design to examine this relationship in a project selection context. The results reveal that there is an inverse relationship between payoff magnitude and the participants’ propensity to take risk with individuals becoming more risk averse as the level of payoff magnitude increases. The study also provides an insight into the key factors considered by risk averse and risk taking managers when making project selection decisions.
Keywords: Payoff magnitude; Propensity to take risk; Project selection